ACUPRESSURE AS A STABILITY OF BLOOD SUGAR IN PATIENTS WITH TYPE II DIABETES MELLITUS: A LITERATURE REVIEW - Nuriya, Nuriya; Taufik, Agis (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Introduction: Diabetes Mellitus (DM) is a chronic disease that is sweeping the world. More than 300 million people in the world suffer from this disease and the number is increasing rapidly. Management and treatment of diabetes involves both pharmacological and non-pharmacological methods. One of the non pharmacological methods is acupressure. Purpose: to find out the benefits of acupressure therapy in health practice and it is hoped that this study can be an illustration of alternative therapies to overcome health problems such as type II diabetes mellitus. Methods: This systematic review was carried out in accordance with the PICO model. The database or database search in this literature review was carried out in April 2022. The database used was Google. A total of 5 articles were used as research samples that met the inclusion and exclusion criteria. Results: 4 out of 5 articles analyzed stated that acupressure was considered to help lower blood glucose levels. Meanwhile, in one article, it was stated that there was no significant difference between the mean glucose levels of the three groups before and after the intervention. Discussion: Self-acupressure at 4 points LIV 3, ST36 SP6 and KD 3 under controlled conditions can increase insulin levels. Acupressure therapy was carried out routinely at ST 36 points and Suzana's feet 3 times on the 6th day, 12th day and 18th day. Emphasis on points ST-36 and SP-6 can restore the balance of Yin and Yang and improve insulin secretory function in patients with non-insulin dependent diabetes mellitus. Conclusion: Acupressure therapy can reduce blood glucose levels in type II DM patients. Acupressure therapy must be carried out according to the correct and regular procedure to avoid failure in acupressure therapy.